Legal Protection for Victims of Artificial Intelligence Misuse in the Form of Deepfake Technology - Widiartana, Gregorius; Lumbanraja, Ebenhaezar Parlindungan (CV. Rayyan Dwi Bharata, 2025)
The development of technology has reached the Fourth Industrial Revolution, marked by the integration of information technology into the industrial world. In this era, information technology plays a crucial role in human daily activities, including the presence of artificial intelligence as a tool to assist human activities in the digital age. Artificial intelligence is like a double-edged sword—it can help humans fulfill their needs, but on the other hand, it can also harm them if misused. One form of artificial intelligence misuse is through deepfake technology. This AI-driven technology, which can manipulate a person’s facial visuals in both video and photo formats, is increasingly being exploited by irresponsible parties. This article discusses legal protection for victims of deepfake misuse, focusing on regulations, resolution mechanisms, and the right to be forgotten. This research employs a normative legal research method with a conceptual approach. The findings of this study indicate that legal protection for victims of deepfake misuse can be achieved through strengthening regulations on AI usage, adopting a restorative justice approach for victims, and ensuring the right to be forgotten to safeguard their online reputation.